Effects of total replacement of corn silage with sorghum silage on milk yield, composition, and quality. Issue 1 (December 2017) - Cattani, M.; Guzzo, N.; Mantovani, R.; Bailoni, L.
Abstract Background In the last years, difficulties occurring in corn cultivation (i.e., groundwater shortages, mycotoxin contamination) have been forcing dairy farmers to consider alternative silages. Some experiments conducted on lactating cows have proven that the total replacement of corn silage with sorghum silage did not reduce milk yield. However, this kind of substitution involves supplementing sorghum-based diets with grains, to compensate for the lower starch content of sorghum silage compared to corn silage. Change of silage type and inclusion of starch sources in the diet would influence rumen fermentations, with possible effects on milk composition (i.e., fatty acid profile) and coagulation properties. A worsening of milk coagulation properties would have a negative economic impact in Italy, where most of the milk produced is processed into cheese. This study was designed to compare milk composition and quality, with emphasis on fatty acid profile and coagulation properties, in dairy cows fed two diets based on corn or sorghum silage. Results The sorghum diet reduced milk yield (P  = 0.043) but not 4% fat corrected milk (P  = 0.85). Feeding sorghum silage did not influence milk contents of protein (P  = 0.07) and lactose (P  = 0.65), and increased fat content (P  = 0.024). No differences emerged for milk concentrations of saturated (P  = 0.61) and monounsaturated fatty acids (P  = 0.50), whereas polyunsaturated fatty acids were lower (P  < 0.001) for the sorghum diet. Concentrations of n-6 (P  < 0.001) and n-3 fatty acids (P  = 0.017) were lower in milk of cows fed the sorghum diet. Milk coagulation properties did not differ between the two diets, except the "a30" (the curd firmness, expressed in mm, 30 min after rennet addition), that was lower (P  = 0.042) for the sorghum diet. Conclusions Feeding a forage sorghum silage, properly supplemented with corn meal, as total replacement of corn silage maintained milk composition and did not influence negatively milk coagulation properties, which have a great economic relevance for the Italian dairy industry. Thus, silages obtained from forage sorghums could have a potential as substitute of corn silages in dairy cow diets.